Body Dissatisfaction Ditinjau dari Social Comparison pada Siswi Sekolah Menengah Atas - Hari Nugraha Putra; Achmad Irvan Dwi Putra; Atrizka Diny (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
This study aims to determine the relationship between social comparison and body dissatisfaction of adolescent. The hypothesis proposed in this research is there any positive correlation between social comparison and body dissatisfaction of senior high school student in SMA Pangeran Antasari Medan, assuming that the higher body dissatisfaction, the higher the social comparison, and vice versa. The sample of this research is as many as 165 students. This research used body dissatisfaction and social comparison scale. Product Moment (Pearson Correlation) was used to analyze the correlation between two variables using SPSS 20 for windows. The results of the data analysis showed that the correlation coefficient was 0,308 with a significance value of 0.000 (p <0.05). It shows that there is a positive correlation between social comparison and body dissatisfaction. The results of this study indicate that the contributions made by the variable of social comparison on personal adjustment was 9,5 percent, while the remaining 90,5 percent was influenced by other factors that were not examined. From these results, it is concluded that the hypothesis, which stated that there is a positive relationship between the social comparison and body dissatisfaction, is acceptable.